Peripartal alterations of calcitonin gene‐related peptide and minerals in dairy cows affected by milk fever. (4th March 2013) - Zebeli, Qendrim; Beitz, Donald C.; Bradford, Barry J.; Dunn, Suzanna M.; Ametaj, Burim N.
<x xml:space="preserve">Abstract</x> Background Milk fever, a metabolic disease of dairy cattle, is associated with perturbations of calcium homeostasis, the pathogenesis of which is not yet completely understood. Objective The aim of this study was to investigate plasma concentrations of calcitonin gene‐related peptide and selected minerals and metabolites in periparturient cows with and without milk fever. Methods Plasma concentrations of calcitonin gene‐related peptide, as well as calcium, phosphate, magnesium, iron, glucose, lactate, and cortisol, were determined in multiple plasma samples from Jersey cows with and without spontaneous milk fever. Results Cows affected by milk fever (n = 5) had lower concentrations of calcitonin gene‐related peptide (P = .038) and inorganic phosphate (P < .001) in plasma than did the controls (n = 5). Also, these cows tended to have lower calcium concentrations (P = .071). Magnesium, iron, lactate, glucose, and cortisol concentrations were comparable between both groups of cows (P > .10). Around the day of calving, plasma concentrations of lactate, glucose, and cortisol increased and the concentration of iron decreased in all cows (P ≤ .01). Conclusions Despite the limited number of cows evaluated, this report is the first to indicate lowered concentrations of calcitonin gene‐related peptide as part of the metabolic changes during milk fever in cows. Further work with a larger cohort of animals is warranted to understand the precise role of calcitonin gene‐related peptide and the potential associations with disturbances in plasma minerals typically observed during milk fever.